The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s11356-014-2816-9
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of insecticide leaching from potted nursery stock and aquatic health benefits of bioretention cells receiving nursery runoff

Abstract: Tree nurseries and greenhouses within the USDA red imported fire ant (RIFA) quarantine zone are required to incorporate insecticides into their potting media to prevent artificial spread of RIFA. Bifenthrin and fipronil are two common insecticides that are incorporated into potting media. During irrigation and stormwater events, there is potential for insecticides to leach from nursery pots, resulting in the contamination of nearby surface waters. In this study, occurrences of insecticides in simulated nursery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Isoxaben was present in runoff water at higher concentrations in the granular formulation compared to the sprayable formulation, most likely due to adsorption of the sprayable isoxaben following application, whereas the granules were dissolved with each irrigation application and with runoff before adsorption could occur (Briggs et al, 2002). Pesticides can be broadcast over the entirety of the production surface area, covering plants, containers, and interspace areas; applied to target locations, for example, postemergence herbicide applications; or incorporated as part of a container substrate mix (Graves et al, 2014). Agrochemicals applied as broadcast applications are more likely to be exported because they have fewer areas and opportunities for adsorption, whereas those applied to plants or in container substrates typically move through the substrate, where adsorption can occur, before being exposed to leaching events (Mahnken et al, 1999).…”
Section: Application Methods and Formulationmentioning
confidence: 99%
“…Isoxaben was present in runoff water at higher concentrations in the granular formulation compared to the sprayable formulation, most likely due to adsorption of the sprayable isoxaben following application, whereas the granules were dissolved with each irrigation application and with runoff before adsorption could occur (Briggs et al, 2002). Pesticides can be broadcast over the entirety of the production surface area, covering plants, containers, and interspace areas; applied to target locations, for example, postemergence herbicide applications; or incorporated as part of a container substrate mix (Graves et al, 2014). Agrochemicals applied as broadcast applications are more likely to be exported because they have fewer areas and opportunities for adsorption, whereas those applied to plants or in container substrates typically move through the substrate, where adsorption can occur, before being exposed to leaching events (Mahnken et al, 1999).…”
Section: Application Methods and Formulationmentioning
confidence: 99%
“…Additives to bioretention and/or greenroof media or pervious pavement mixtures or subbase material has also been shown to improve removal of targeted pollutants. Amendments such as fly ash, biochar, iron slag, activated carbon, wood chips, and compost in bioretention and/or greenroof media have been shown to improve retention of phosphorus, bacteria, metals, pesticides, and/or other pollutants (Zhang et al, 2008;Beck et al, 2011;Penn et al, 2011;Palmer et al, 2013;Graves et al, 2014;Paus et al, 2014;Iqbal et al, 2015;Lee et al, 2015;Peterson et al, 2015;Ulrich et al, 2015). Additives to pervious concrete have also been shown to improve retention of pollutants including phosphorus, heavy metals, and bacteria (Park and Tia, 2004;Jo et al, 2015;Vázquez-Rivera et al, 2015).…”
Section: Critical Review Questionsmentioning
confidence: 99%
“…The combination of frequent irrigation, absence of landscape vegetation, and application of a variety of pesticides and fertilizers creates a scenario conducive to pesticide and nutrient loading in receiving water bodies (Briggs, Riley, & Whitwell, ). Pesticide concentrations in pot leachate can be toxic to aquatic organisms (Graves, Vogel, Belden, Rebek, & Simpson, ). For example, Wilson, Riiska, and Albano () found that 29% of chlorothalonil application in a nursery setting was deposited on the ground surface instead of in pots, which led to concentrations up to 500 μg L −1 in runoff, a level toxic to aquatic microorganisms (e.g., 96‐h LC 50 , the concentration that will kill half of a test population, for adult grass shrimp is 150 μg L −1 according to Key, Meyer, & Chung, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although contaminants of concern are similar between nursery and other agriculture runoff, hydrology and hydraulic loading differs due to frequent irrigation events on plant nurseries. Also, pot leachate presents potential for continued loading of pesticides and nutrients during every runoff event (Graves et al., ).…”
Section: Introductionmentioning
confidence: 99%